Whole-Genome Sequencing-Based Antimicrobial Resistance Characterization and Phylogenomic Investigation of 19 Multidrug-Resistant and Extended-Spectrum Beta-Lactamase-Positive Escherichia coli Strains Collected From Hospital Patients in Benin in 2019 - Yehouenou, Carine Laurence; Bogaerts, Bert; De Keersmaecker, Sigrid C. J.; Roosens, Nancy H. C.; Marchal, Kathleen; Tchiakpe, Edmond; Affolabi, Dissou; Simon, Anne; Dossou, Francis Moise; Vanneste, Kevin; Dalleur, Olivia (Frontiers in Microbiology, 2021)
The increasing worldwide prevalence of extended-spectrum beta-lactamase (ESBL) producing Escherichia coli constitutes a serious threat to global public health. Surgical site infections are associated with high morbidity and mortality rates in developing countries, fueled by the limited availability of effective antibiotics. We used whole genome sequencing (WGS) to evaluate antimicrobial resistance and the phylogenomic relationships of 19 ESBL-positive E. coli isolates collected from surgical site infections in patients across public hospitals in Benin in 2019. Isolates were identified by MALDI-TOF mass spectrometry and phenotypically tested for susceptibility to 16 antibiotics. Core-genome multi-locus sequence typing and Single Nucleotide Polymorphism-based phylogenomic methods were used to investigate the relatedness between samples. The broader phylogenetic context was characterized through the inclusion of publicly available genome data. Among the 19 isolates, thirteen different sequence types (STs) were observed, including ST131 (n=2), ST38 (n=2), ST410 (n=2), ST405 (n=2), ST617 (n=2) and ST1193 (n=2). The blaCTX-M-15 gene encoding ESBL resistance was found in 15 isolates (78.9%), as well as other genes associated with ESBL such as blaOXA-1 (n=14) and blaTEM-1 (n=9). Additionally, we frequently observed genes encoding resistance against aminoglycosides (aac-(6’)-Ib-cr, n=14), quinolones (qnrS1, n=4), tetracyclines (tet(B), n=14), sulfonamides (sul2, n=14) and trimethoprim (dfrA17, n=13). Nonsynonymous chromosomal mutations in the housekeeping genes parC and gyrA associated with resistance to fluoroquinolones were also detected in multiple isolates. Although the phylogenomic investigation did not reveal evidence of hospital-acquired transmissions, we observed two very similar strains collected from patients in different hospitals. By characterizing a set of multidrug-resistant isolates collected from a largely unexplored environment, this study highlights the added value for WGS as an effective early warning system for emerging pathogens and antimicrobial resistance.